Penguatan Budaya Literasi Mahasiswa melalui Workshop Instrumen Pengenalan Lapangan Persekolahan (PLP) Berbasis Unity of Sciences - Listyono Listyono; Arifah Purnamaningrum (Universitas Mathla'ul Anwar Banten, 2022)
EMPOWERING STUDENT’S LITERACY CULTURE TROUGH INSTRUMENT WORKSHOP OF SCHOOL INTRODUCTION PROGRAM (PENGENALAN LAPANGAN PERSEKOLAHAN OR PLP) BASED ON UNITY OF SCIENCES. The development of instrument for the PLP program at UIN Walisongo Semarang and its socialization need to be done. The purpose of this service activity is to develop a Unity of Science-based PLP instrument and socialize it to students. The implementation of this service activity includes team formation, instrument design, instrument validation and instrument socialization workshops. The development of the instrument refers to the Research and Development (R & D) method. For socialization to students delivered through workshops. The achievement of strengthening literacy culture is measured through a questionnaire. The results of this activity were instrument for the PLP program at UIN Walisongo Semarang has developed. It has shared to the students. The students are familiar with the PLP program and its instruments based on Unity of Sciences. Students stated that they obtained the information from several sources, including from lecturers, seniors, friends, social media, guardianship books, informants from other universities, and articles. The strengthening of qur'an and hadith literacy of students also increased. The conclusion of this service was student’s literacy for Qur’an and Hadith have increase and student’s insight to PLP instrument escalated.